Urgensi Penegasan Pancasila sebagai Dasar Nilai Pengembangan Iptek - Ika Setyorini (Fakultas Syari'ah dan Hukum (FSH) UNSIQ, 2018)
Pancasila as a state ideology is the crystallization of cultural values, the religion of the Indonesian people. So that these values will accommodate all activities of life as a nation and state society. Like wise in scientific activities. In the development of Science Technology in Indonesia based on the five precepts in the Pancasila is a guide and guide and development of science and technology. So that it is hoped that through this paper it is hoped that Pancasila as the basis for the value of science and technology development can become normative guidelines for the development of science in Indonesia.